Growth Pattern in Chinese Children With 5α-Reductase Type 2 Deficiency: A Retrospective Multicenter Study - Zhao, Xiu; Song, Yanning; Chen, Shaoke; Wang, Xiumin; Luo, Feihong; Yang, Yu; Chen, Linqi; Chen, Ruimin; Chen, Hui; Su, Zhe; Wu, Di; Gong, Chunxiu (Frontiers in Pharmacology, 2019)
Background: 5α - reductase type 2 deﬁciency (5αRD) is an autosomal recessive hereditary disease which has an incidence of 11.2%-15.5% among population with 46, XY DSD (disorders of sex development). Objective: To study the growth pattern in Chinese pediatric patients with 5αRD. Subjects: Data were from 187 patients with 5αRD (age from 0-16 years old) who visited 8 pediatric endocrine centers from Jan, 2010 to Dec, 2017. Children with 46, XY DSD without hormone treatment and those with testicular dysfunction were also selected as a positive control group. Methods: Height, weight and other relevant data were collected from the multicenter hospital registration database. Hormone was tested by enzyme enhanced chemiluminescence assay; BA was assessed by G-P. Growth curve was constructed based on λ-median-coefficient of variation method (LMS). Results: Compared to normal boys, higher height standard deviation scores (HtSDS) were observed in 5αRD children who were <1-year-old (p=0.002, 0.048, respectively), and higher weight standard deviation scores (WtSDS) in those < 6-month-old (p=0.012). Then HtSDS and WtSDS showed lower than those of normal boys of the same age when > 2-year-old. The variation tendency of HtSDS in Chinese 5αRDs was consistent with the trend of T after HCG stimulation test. HtSDS and T after HCG stimulation test in the EMS < 7 group were higher than those in the EMS ≥7 group. Additionally, the ratio of bone age over chronological age (BA/CA) was lower than 1 in children with 5αRD. Conclusion: The children with 5αRD had a special growth pattern which was affected by high level of T. Their body length was longer in 0~5 months group, and then its growing slowed down leaving children shorter than normal boys after the age of 2 years old. The bone age was delayed in 5αRD children. This may provide a chance for androgens treatment in young age 5αRD boys for their micropenis.